Dialektika Iman dan Aksi dalam Membentuk Karakter Religius Siswa Melalui Program (UPL) Ujian Praktik Lapangan di Madrasah Aliyah Hikmatul Hasanah Bulujaran Kidul Tegalsiwalan Probolinggo - Izzatul Laili; Herwati; Yeniati Ulfah (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the dialectic of faith and action in shaping students' religious character through the Field Practice Exam (UPL) program. This research is motivated by the importance of connecting students' religious understanding with real-life practices. The study used a qualitative approach with descriptive methods to describe in depth the program's implementation process. Data collection techniques included observation, interviews, and documentation of the implementation of the field practice exam program. The results showed that the field practice exam plays a significant role in connecting students' understanding of faith with real-life actions, such as patience in facing difficulties in the field, discipline and responsibility (Amanah) in carrying out tasks, maintaining worship amidst busy practice, and being honest and having good morals in interacting with others during the field practice. The dialectic of faith and action is evident when students' religious values ​​encourage religious behavior, while practical experiences in the field also strengthen students' faith and religious awareness. In addition, the UPL program provides students with direct experience in implementing religious values ​​in social life. Thus, field practice learning becomes an effective means of internalizing religious values ​​and continuously shaping students' religious character